2020
DOI: 10.3390/ijms21218355
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Study, Dual Anti-Bactericidal and Anti-Viral Effects and Molecular Docking of Cobalt(III) Complexes

Abstract: Considering our previous findings on the remarkable activity exhibited by cobalt(III) with 2-acetylpyridine-N(4)-R-thiosemicarbazone (Hatc-R) compounds against Mycobacterium tuberculosis, the present study aimed to explored new structure features of the complexes of the type [Co(atc--R)2]Cl, where R = methyl (Me, 1) or phenyl (Ph, 2) (13C NMR, high-resolution mass spectrometry, LC–MS/MS, fragmentation study) together with its antibacterial and antiviral biological activities. The minimal inhibitory and minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Cobalt(III) is an endogenous metal, and therefore, the bioavailability of cobalt(III)-like compounds can be increased, as well as their biological properties, in therapeutic protocols for human diseases [ 31 , 60 ]. Considering the chemical versatility of the synthesis of TSC and the biological properties of cobalt(III)-like compounds, we previously analyzed complexes of the type [Co III (atc–R) 2 ]Cl which demonstrated interesting antibacterial and antiviral activities [ 33 ]. Here, we characterized the anti-CHIKV activity of the [Co III (L 1 ) 2 ]Cl, a Cobalt(III) coordination compound with the thiosemicarbazone ligand with promising antiviral proprieties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cobalt(III) is an endogenous metal, and therefore, the bioavailability of cobalt(III)-like compounds can be increased, as well as their biological properties, in therapeutic protocols for human diseases [ 31 , 60 ]. Considering the chemical versatility of the synthesis of TSC and the biological properties of cobalt(III)-like compounds, we previously analyzed complexes of the type [Co III (atc–R) 2 ]Cl which demonstrated interesting antibacterial and antiviral activities [ 33 ]. Here, we characterized the anti-CHIKV activity of the [Co III (L 1 ) 2 ]Cl, a Cobalt(III) coordination compound with the thiosemicarbazone ligand with promising antiviral proprieties.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that the treatment of CHIKV-infected cells with the cobalt(III)-conjugated thiosemicarbazone [Co III (L 1 ) 2 ]Cl (Fig. 1 ) reduced CHIKV infection, and cell viability was not affected compared to the treatment with its organic ligand [ 33 ]. In this work, [Co III (L 1 ) 2 ]Cl had its antiviral activity characterized using a recombinant CHIKV engineered to express the nanoluciferase reporter (CHIKV- nanoluc ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They revealed promising MIC and MBC values which ranged from 0.39 to 0.78 μg/mL found in two tested strains and presented high potential against CHIKV by reducing viral replication up to 80%. In addition, the molecular docking analysis was performed whereas, the relative binding energy of the docked compound with five bacteria strains was found in the range of Ε = 3.45 and Ε = 9.55 kcal/mol [28] .…”
Section: Introductionmentioning
confidence: 99%